PENGARUH PENGGUNAAN METODE EKSPERIMEN TERHADAP MINAT, KEAKTIFAN DAN HASIL BELAJAR PADA MATERI GELOMBANG BUNYI SISWA KELAS XII IPA1 SMA NEGERI 1 RAJA AMPAT KABUPATEN RAJA AMPAT - IRIYANTI, EKA; VIRMAN, VIRMAN (Jurnal Ilmu Pendidikan Indonesia, 2018)
The purpose of this research is to know: (1) influence of experimental method to study interest, (2) influence of experiment method to learning activity, (3) influence of experiment method to learning result, (4) improvement of learning result on wave material the sound of class XII students IPA1 SMA Negeri 1 Raja Ampat Raja Ampat District. This type of research is a correlational quantitative research. The sample in this study is the students of class XII IPA1 SMA Negeri 1 Raja Ampat Raja Ampat Regency which amounted to 35 students. The result of the research shows that (1) there is a strong influence between experimental method of using learning method equal to r = 0,709 with contribution 50,3%, while the influence of experiment method to learning interest is (tct = 5,774)> (ttable = 1,697 ) or significance value 0.00 <0.05, (2) there is a strong influence between experimental method of using learning method r = 0,854 with donation equal to 73%, while the influence of experiment method to learning activity is (tct = 9,437)> (ttabel = 1,697) or significance value 0.00 <0.05, (3) there is a strong influence between the variables of the use of experimental methods on learning outcomes of r = 0,531 with a contribution of 28.2%, while the amount of influence of use experimental method of learning result is (tct = 9,437)> (ttable = 1,697) or significance value 0,00 <0,05, (4) there is improvement of result lecture on the matter of sound waves of students of class XII IPA1 SMA Negeri 1 Raja Ampat Raja Ampat District of 0.58 which is included in the medium category